O ensino de astronomia na formação de professores de física - Lopes, Kamilla Ventura da Silva (2017)
Education in Astronomy is still little experienced in Brazil. The degree courses in Physics that, in principle, should also contemplate Astronomy-related contents, do not deal with this science in compulsory courses. In some lessons, subjects clearly related to Astronomy are part of the content of elective academic disciplines, although there is a growing interest in investigations on the subject in postgraduate studies. Considering that knowledge about Astronomy can also be explored in Physics, as additional activities, we had the interest to develop a didactic workshop on Astronomy-related topics, oriented to some ungraduated students of the Institutional Program of Initiation to Teaching (PIBID) of Physics in the Federal University of Tocantins, at the Araguaína Campus. The activities developed with the students were planned in workshop format, duly preceded by a bibliographical survey. Through the use of questionnaires, games, experiments, telescope for night observation, we seek to motivate students to discuss Astronomy contents, considering the interconnection of this science to daily life, in order to promote the development of skills and abilities described in the Brazilian Curricular Parameters of Elementary School. After the realization of these activities, we inferred that the workshop was effective in arousing students' interest to discussion of concepts on Astronomy and on the importance of the knowledge of this science for the formation of the Physics teacher. We conclude that this type of activity contributes to minimizing the gaps in the initial formation of the physics teacher in relation to basic knowledge about Astronomy.